Enfoques periodísticos y educación en El Comercio, Página/12 y El País en contexto prepandémico (2019) - Gonzales, Carlos (2024)
This study analyzes the representation of education and public policies in the written press and its impact on citizen perception, focusing on El Comercio (Peru), Página/12 (Argentina) and El País (Spain), from May to December 2019 (n = 260). Content analysis and PCA were used to examine the coverage and frames employed. It was found that, Página/12 stands out for an intensive focus on these topics, with Attribution of Responsibility and Conflict frames predominating, indicating a specific editorial orientation. In contrast, El País and El Comercio show a balanced and diverse approach, with notable variations in the use of sources and news presentation. This pre-pandemic analysis underlines the influence of the media on public opinion and educational policies, highlighting the need for a balanced and critical coverage of socially relevant issues.